Ecological and economic linkages between the arid and semi-arid zones: The role of livestock - Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Turner, M.; Williams, Timothy O. (International Crops Research Institute for the Semi-Arid Tropics, 1995)
In this document ILCA proposes a set of six researchable issues pertaining to ILCA's three research areas that need to be investigated (three broad themes). A brief description of the researchable issues is presented. This includes economic and policy measures to improve the management of natural resources for livestock production in the arid zone, croping mechanisms to minimize drought-induced production and capital losses in the arid zone, potential for improving the security and effectiveness of seasonal livestock movements, adaptation of the arid zone vegetation to drought and grazing to better control land degradation and improve reclamation of degraded lands, optimal stocking rates and livestock mobility patterns to control land degradation and vegetation biodiversity losses in the semi-arid zone, and potential for stratification of livestock production.